Reaction mechanism for the dual gold-​catalyzed synthesis of dibenzopentalene: a DFT study - Larsen, Mie Højer; Hashmi, A. Stephen K. (Chemistry - a European journal, 2014)
A wide range of gold-catalyzed reactions based on a dual activation mechanism has recently been reported in the literature. Herein, we present a computational investigation of the mechanism for the formation of dibenzopentalenes from 1-ethynyl-2-(phenylethynyl)benzene. Transition states have been found, which substantiate the dual activation mechanism previously published and furthermore point towards a continuous presence of two gold moieties throughout the mechanistic cycle, an observation of high importance for all reactions in the field of dual activation. The initial activation of the diyne has been shown to proceed via an intermolecular transfer of a cationic gold catalyst from the thermodynamically preferred geminal-σ,π-acetylide complex to the active non-geminal analogue. Furthermore, the regioselectivity of a 5-endo versus a 6-endo cyclization has been addressed, and the 5-endo cyclization was found to be most favorable both thermodynamically and with regard to the activation barrier.
Gesehen am 05.10.2020